The applications of the Kernel densities to modeling the generalized Pareto distributions - Kuźmiński, Łukasz (Zastosowania funkcji jądra gęstości do modelowania uogólnionych rozkładów Pareto, 2013)
In this paper we present the tools used in the modeling of distributions with fat tailsin the theory of extreme values. We present three tools: the sample distribution function, the histograms for grouped data and the kernel densities. The latter is described in detail. The presented examples show the application of the kernel densities to modeling the generalized Pareto distributions.
Ekonometria = Econometrics, 2013, Nr 3 (41), s. 55-64
Keywords: Kernel densities; extreme values; generalized Pareto distributions; funkcje jądra gęstości; wartości ekstremalne; uogólniony rozkład Pareto